2005
DOI: 10.1111/j.1600-0501.2005.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of implant designs: influence of diameter, length, and taper on strains in the alveolar crest

Abstract: If the objective is to minimize peri-implant strain in the crestal alveolar bone, a wide and relatively long, untapered implant appears to be the most favorable choice. Narrow, short implants with taper in the crestal region should be avoided, especially in low-density bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
226
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(270 citation statements)
references
References 32 publications
14
226
2
15
Order By: Relevance
“…Pierrisnard et al [12] found in their study that the stress to which implants were exposed increased as the length of the implant increased (range, 6 to 12 mm) while the maximum bone stress was found to be almost constant. Study of C. S. Petrie et al [13] came to the conclusion that strain near crestal bone area reduces nearly by 300% due to increase in diameter as compared to the 165% reduction due to increase in length of implant. Therefore, comparatively larger diameter of implant design is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Pierrisnard et al [12] found in their study that the stress to which implants were exposed increased as the length of the implant increased (range, 6 to 12 mm) while the maximum bone stress was found to be almost constant. Study of C. S. Petrie et al [13] came to the conclusion that strain near crestal bone area reduces nearly by 300% due to increase in diameter as compared to the 165% reduction due to increase in length of implant. Therefore, comparatively larger diameter of implant design is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies revealed an association of loading conditions with marginal bone loss around oral implants and complete loss of osseointegration. In addition, finite element analysis (FEA) showed that stress on peri-implant tissues occurs under various conditions (3)(4)(5). Kitamura et al (3) found that biomechanical adaptation of bone to stress may result in conical resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Kitamura et al (3) found that biomechanical adaptation of bone to stress may result in conical resorption. Ptrie et al (4) found that if the objective is to minimize peri-implant strain in the crestal alveolar bone, a wide and relatively long untampered implant is the best choice. Baggi et al (5) reported that cortical peri-implant areas vulnerable to overloading were affected primarily by implant diameter, irrespective of bone-implant interface length.…”
Section: Introductionmentioning
confidence: 99%
“…The mode of retention of the Locator attachments is frictional contact, which arises from a dimensional misfit between the slightly oversized nylon male insert and the smaller diameter of the inner ring of the female abutment 21) . Reviewing the literature, the effect of implant diameter on peri-implant crestal strain was investigated in several finite element studies (FEA) 2,9,14,15,[22][23][24][25][26][27][28] . However, FEA has several drawbacks.…”
Section: Introductionmentioning
confidence: 99%